2019
DOI: 10.1002/asia.201901169
|View full text |Cite
|
Sign up to set email alerts
|

4‐Methyltetrahydropyran (4‐MeTHP): Application as an Organic Reaction Solvent

Abstract: 4-Methyltetrahydropyran (4-MeTHP) is ah ydrophobic cyclic ether with potential for industrial applications. We herein report, for the first time, ac omprehensive study on the performance of 4-MeTHP as an organic reaction solvent. Its broad application to organic reactions includes radical, Grignard, Wittig, organometallic, halogen-metal exchange, reduction,o xidation, epoxidation, amidation, esterification, metathesis, and other miscellaneous organic reactions. This breadth suggests4 -MeTHP can serve as a subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 65 publications
1
42
0
Order By: Relevance
“…(E)-1-Bromo-3,7-dimethylocta-2,6-diene 19c, yield 84%. The spectral data were consistent with those in the literature [49].…”
Section: General Procedures For Synthesis Of Bromidessupporting
confidence: 90%
“…(E)-1-Bromo-3,7-dimethylocta-2,6-diene 19c, yield 84%. The spectral data were consistent with those in the literature [49].…”
Section: General Procedures For Synthesis Of Bromidessupporting
confidence: 90%
“…Green chemistry is an increasing trend not only in chemical industry but also in academia. 59 62 Despite the environmental needs and the availability of many alternative solvents such as water, 63 ethyl acetate, 64 , 65 dimethyl carbonate, 66 , 67 2-MeTHF, 68 , 69 and 4-MeTHP, 61 , 70 the usage of green solvent for olefin metathesis is relatively scarce. We therefore screened both the general-purpose Hoveyda–Grubbs second-generation catalyst ( Ru1 , see Figure 1 ) and the tagged StickyCat PF 6 ( Ru2 ) in RCM of diethyl diallylmalonate ( 1 ) used as a model substrate, in two solvent systems—DCM (not green) and EtOAc (green).…”
Section: Results and Discussionmentioning
confidence: 99%
“…4-MeTHP can be utilized under acidic or alkaline conditions, thus it is being used as a solvent in esterifications, radical reactions, Grignard and Wittig reactions, halogen-metal exchange, in reductions and oxidations, including epoxidation, and many other organic reactions. 45 Due to all these advantages and green chemistry perspectives, it is expected that this solvent will find a broad range of applications, especially in industrial processes, as it was suggested in an elegant exploratory study by Kobayashi et al 45 To the best of our knowledge, however, 4-MeTHP has not yet been tested in olefin metathesis reactions promoted by modern second-generation catalysts. 46…”
Section: Introductionmentioning
confidence: 99%